2013
DOI: 10.5826/dpc.0302a06
|View full text |Cite
|
Sign up to set email alerts
|

A tiny invasive melanoma: a case report with dermatoscopy and dermatopathology

Abstract: We present a case of an early invasive melanoma (Breslow thickness 0.25 mm), 1.6 mm in diameter on the arm of a 38-year-old woman. She was under surveillance due to having multiple (>100) nevi, and the melanoma was assessed as a new lesion by the examining doctor. Clinically the lesion was hyper-pigmented compared with surrounding nevi and dermatoscopically it had a clue of pseudopods/lines radial, but they were arranged in an arguably symmetrical circumferential pattern around a structureless blue-gray center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Previously dermatoscopic features of four minute melanomas with a diameter of 1.5–2 mm were reported . One of these minute melanomas was invasive . The present case, with a maximum diameter of 0.9 mm, is the smallest melanoma that has ever been reported, and it presented as a changing lesion on an adult with dermatoscopic subtle gray color, these features being sufficient according to the Chaos and Clues algorithm to warrant excisional biopsy.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Previously dermatoscopic features of four minute melanomas with a diameter of 1.5–2 mm were reported . One of these minute melanomas was invasive . The present case, with a maximum diameter of 0.9 mm, is the smallest melanoma that has ever been reported, and it presented as a changing lesion on an adult with dermatoscopic subtle gray color, these features being sufficient according to the Chaos and Clues algorithm to warrant excisional biopsy.…”
mentioning
confidence: 52%
“…Previously dermatoscopic features of four minute melanomas with a diameter of 1.5–2 mm were reported . One of these minute melanomas was invasive .…”
mentioning
confidence: 95%
“…It has previously been reported that small melanomas may not be asymmetrical [1,2]. It has also been reported that hyperpigmentation was the defining feature in all of 13 small melanomas (<4 mm diameter) in one series of 95 melanomas [12], but Pellizzari et al pointed out that this may in fact be due to selection bias, with darker lesions being discovered, while paler, hypomelanotic lesions may not be suspected at the stage where they are very small [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Another recent case report by Pellizzari et al suggests that in very small lesions chaos (asymmetry of structure or color) may not be unequivocally present [2]. This particular melanoma had the diagnostic clue of lines radial, but as with the smallest published invasive melanoma [2], the radial lines were distributed circumferentially and any asymmetry was equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…По результатам гистологического исследования, все опухоли были представлены поверхностно-распространяющейся формой меланомы, а шесть образований были in situ [7]. В зарубежной литературе [8][9][10] встречаются описания единичных случаев меланомы кожи диаметром не более 2 мм.…”
Section: рис 7 пациент №10unclassified